Estimation of Plasma Triglyceride Level among Patients with Diabetes Mellitus, Wad Medani, Gezira State, Sudan, in 2022 - GadAllah Modawe; Algili Alblal; Almigdad Ibrahim; Eman Mohy Aldein; Suhair A. Ahmed; AbdElkarim A. Abdorabo; Khalid Eltahir Khalid (Sirte Journal of Medical Sciences, 2024)
Background: In Sudan and around the world, Diabetes Mellitus is a growing health concern. It is a serious, ongoing condition. The Middle East and North Africa area (MENA) area, which includes Sudan, has the world’s highest prevalence of diabetes. It was predicted to be about 25%. More concerning is the prediction that by 2030. Patients and Methods: This is a case control study conducted in Aldaraga Health Center for Diabetes Care and Wad Medani Pediatric Teaching Hospital, Wad Medani, Gezira State, Sudan to estimate the plasma triglyceride level among diabetic patients. A total of 160 participants were included in the study, ninety patients were case group (Diabetic patients), their mean age was (40.90±24.00) years and seventy were control group (Healthy individuals) their mean age was (45.78±22.38) years. Among case, 37 (41%) were males while 53 (59%) were females. Data were collected by using questionnaire and analyzed by computer program SPSS (Version 20). After fasting (8-12) hours, 2 ml of heparinized plasma and 1.5 ml EDTA whole blood was collected for estimation of triglyceride and HbA1c respectively and then plasma was stored at -200C till assay was done by Cobas C 311. Results: It revealed high rate of poor glycemic control in Sudanese diabetic patients (81%). There were significance differences in plasma triglyceride between diabetic patients and control group (P value =0.002), age groups (P value =0.000), and gender (P value =0.019). However, there were no statistically significant differences when compared plasma triglyceride levels with glycosylated hemoglobin and duration of the disease (P values = 0.514 and 0.096 respectively). Conclusion: Diabetes, age, and gender, but not glycosylated hemoglobin or disease duration, were found to have an impact on triglyceride levels in this study.